Emerging trends and focus on immune checkpoint inhibitors for non-small cell lung cancer treatment: visualization and bibliometric analysis - Zhang, Yue; Lu, Lishan; Zheng, Rui (Frontiers in Pharmacology, 2023)
Background: Lung cancer is the leading cause of cancer-related deaths worldwide, and non-small cell lung carcinoma (NSCLC) accounts for approximately 80% of all cases. Immune checkpoint inhibitors (ICIs) are widely used to treat NSCLC because of their remarkable efficacy. In this study, we analyzed the scientific collaboration network, defined the hotspots of ICIs for NSCLC research and its evolution over the past few years, and forecasted the field's future development using bibliometric analysis and a graphical study. Methods: The articles and reviews regarding ICIs for NSCLC were retrieved and obtained from the Web of Science Core Collection (WOSCC) on September 26, 2022. CtieSpace and VOSviewer were used to conduct the bibliometric and knowledge-map analysis. Results: We included 8,149 articles for this literature analysis. Our results showed that the USA had the highest number of publications and citations. We noted that research trends changed drastically over the last 20 years, from the early development of ICIs such as CTLA-4 inhibitors to recent ones such as PD-1 and PD-L1 blockers. The focus of research has gradually shifted from mechanisms to treatment effects and adverse events. These results suggest that this field is maturing, and clinical applications are being explored, including how to enhance efficacy, reduce adverse effects, and expand to other specific cancer types. Conclusion: This study is the first to construct a comprehensive knowledge map on ICIs for NSCLC. It can help researchers rapidly grasp the status and focus of current research in this area, offer direction, and serve as a reference for conducting similar studies.